Couples' Parental Leave Practices The Role of the Workplace Situation - Trude Lappegård (Statistics Norway, Research Department, 2008)
We address the issue of the relationship between couples' parental leave practices and their workplace situation. This analysis is based on information from Norwegian administrative registers on around 200 000 couples, covering a period of almost 10 years. The most common practice among couples is that a father makes use of his exclusive right to father's leave and the mother uses all common leave. There are few obstacles in fathers' workplaces limiting father's leave, except in workplaces where there are high costs involved. Parental leave practices involving couples sharing part of their common leave are associated both with mothers' workplaces, with higher costs of absence, and fathers' workplaces, with lower costs of absence.
Keywords: I38; J18; 330; gender; parenthood; parental leave; work